Long-term follow-up results after autologous haematopoietic stem cell transplantation for severe systemic sclerosis. Issue 1 (25th May 2007) - Vonk, M C; Marjanovic, Z; van den Hoogen, F H J; Zohar, S; Schattenberg, A V M B; Fibbe, W E; Larghero, J; Gluckman, E; Preijers, F W M B; van Dijk, A P J; Bax, J J; Roblot, P; et al.
Abstract : Objective: Systemic sclerosis (SSc) is a generalised autoimmune disease, causing morbidity and a reduced life expectancy, especially in patients with rapidly progressive diffuse cutaneous SSc. As no proven treatment exists, autologous haematopoietic stem cell transplantation (HSCT) is employed as a new therapeutic strategy in patients with a poor prognosis. This study reports the effects on survival, skin and major organ function of HSCT in patients with severe diffuse cutaneous SSc. Patients and methods: A total of 26 patients were evaluated. Peripheral blood stem cells were collected using cyclophosphamide (4 g/m2 ) and rHu G-CSF (5 to 10 μg/kg/day) and were reinfused after positive CD34+ selection. For conditioning, cyclophosphamide 200 mg/kg was used. Results: After a median follow-up of 5.3 (1–7.5) years, 81% (n = 21/26) of the patients demonstrated a clinically beneficial response. The Kaplan–Meier estimated survival at 5 years was 96.2% (95% CI 89–100%) and at 7 years 84.8% (95% CI 70.2–100%) and event-free survival, defined as survival without mortality, relapse or progression of SSc, resulting in major organ dysfunction was 64.3% (95% CI 47.9–86%) at 5 years and 57.1% (95% CI 39.3–83%) at 7 years. Conclusion: This study confirms that autologous HSCT in selected patients with severe diffuse cutaneous SSc results in sustained improvement of skin thickening and stabilisation of organ function up to 7 years after transplantation.